Controle da Camarotella torrendiella e Camarotella acrocomiae no cultivo do Cocos nucifera - Pinto, Jailson Mauricio (2023)
The coconut tree, Cocos nucifera, is one of the most cultivated plant species in the world. It is widespread in more than two hundred countries. In Brazil, Ceará has the highest production of the fruits, followed by Bahia, Sergipe, Pernambuco, Espírito Santo, Alagoas, Rio Grande do Norte, Paraíba, Minas Gerais, Piauí and Maranhão. One of the main diseases reported in the literature regarding cocoiculture is sandpaper, caused by the fungus Camarotella torrendiella and Camarotella acrocomiae. The disease can cause losses of up to 50% of production. The research, through the experiments mounted on the "Fazenda coco verde mata sede", Km 28, São Mateus/ES, aimed to analyze the efficacy of fungicide based on Ciproconazole, with the organomineral fertilizer, Agromós, and two products not yet registered with the Ministry of Agriculture, Livestock and Supply, waiting to be registered as organomineral fertilizers, denominated ASD 2022 and ASV 2022, respectively. For the experiment, a randomized block design was used, with plots subdivided in time, with three plants, nine treatments and six replications, totaling one hundred and sixty-two plants. The products were applied in different doses. Each treatment was evaluated for the number of leaves and the presence of sandpaper. It was sought to find the best combination of the mixture of the fungicide with organimineral products, for the control of the disease in the field, optimizing the cost-benefit. The research was conducted from: 02/09/2022 to 07/15/2023, totaling four applications, eight collections referring to the average of leaves per treatment and the average of the first leaf with sandpaper. For the number of leaves, there were no statistically significant changes compared with the control, while for the analysis of the first leaf with sandpaper, it obtained significant results in comparison with the control, with a gain of more than three leaves without the presence of sandpaper per treatment in relation to the control.